2013
DOI: 10.2134/agronj2012.0467
|View full text |Cite
|
Sign up to set email alerts
|

Maize Nutrient Accumulation and Partitioning in Response to Plant Density and Nitrogen Rate: I. Macronutrients

Abstract: Understanding nutrient balances in changing cropping systems is critical to appropriately adjust agronomic recommendations and inform breeding efforts to increase nutrient efficiencies. Research to determine the season‐long P, K, and S uptake and partitioning dynamics in maize (Zea mays L.) as affected by low, medium, and high plant density (PD) and N rate factors and their interactions was conducted over four site‐years in Indiana. Plant nutrient contents at maturity responded predominantly to N rate. Relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
118
4
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(138 citation statements)
references
References 61 publications
8
118
4
8
Order By: Relevance
“…The irrigation regimes did not significantly affect the slopes of these relationships (p=0.21). The P concentration in relation to N in maize under non-limiting N conditions was described by the linear relationship developed by Ziadi et al (2007), Greenwood et al (2008), Bélanger et al (2011) and Ciampitti et al (2013). Bélanger et al (2011) reported linear-plateau relationships between maize and wheat leaf N and P concentrations considering the growing season and linear relationships when considering stem elongation for wheat and silking for maize.…”
Section: Resultsmentioning
confidence: 99%
“…The irrigation regimes did not significantly affect the slopes of these relationships (p=0.21). The P concentration in relation to N in maize under non-limiting N conditions was described by the linear relationship developed by Ziadi et al (2007), Greenwood et al (2008), Bélanger et al (2011) and Ciampitti et al (2013). Bélanger et al (2011) reported linear-plateau relationships between maize and wheat leaf N and P concentrations considering the growing season and linear relationships when considering stem elongation for wheat and silking for maize.…”
Section: Resultsmentioning
confidence: 99%
“…The available nutrients can be used by crop to increase the intended yield. Nutrient balance should be achieved to optimize crop productivity (Ciampitti et al, 2013). The application of fertilizer dose based on recommendation of PUTS device had the highest result.…”
Section: The Influence Of Fertilizing Methods On Two New Superior Varmentioning
confidence: 99%
“…To validate the model an experiment is suggested to compare methodologies. Os aumentos de produtividade da cultura de milho se devem ao desenvolvimento da agricultura com relação ao melhoramento genético das plantas e as práticas de manejo, entre elas, a correção e fertilização dos solos (CIAMPITTI et al, 2013;BENDER et al, 2013). Stewart et al (2005) relataram que 57% do aumento de produtividade da cultura de milho pode ser atribuída as aplicações de corretivos e fertilizantes.…”
Section: Introductionunclassified
“…No entanto, as informações sobre absorção e partição dos nutrientes na cultura de milho são provenientes de literaturas mais antigas (CIAMPITTI et al, 2013). Os trabalhos mais recentes sobre a absorção e partição dos nutrientes na cultura de milho têm sido realizados principalmente nos Estados Unidos (CIAMPITTI; VYN, 2011;CIAMPITTI et al, 2013).…”
Section: Introductionunclassified
See 1 more Smart Citation